Gazing the dusty mirror: Joint effect of narcissism and sadism on workplace incivility via indirect effect of paranoia, antagonism, and emotional intelligence - Wang, Bo; Fiaz, Muhammad; Hayat Mughal, Yasir; Kiran, Alina; Ullah, Irfan; Wisetsri, Worakamol (Frontiers in Psychology, 2022)
Workplace productivity is badly affected by many negative factors such as narcissism, sadism, in addition paranoia and antagonism play important role in increasing the workplace incivility. Through emotional intelligence such negative behaviors could be controlled by managers and their subordinates. The aim of the current study is to investigate the parallel mediating role of paranoia, antagonism and emotional intelligence on the relationship between narcissism, sadism and workplace incivility. Survey approach is used. Primary data is collected in PLS-SEM. population of the study is all faculty members in higher education institutions in KP region. Measurement model and structural models are developed. Measurement model explained that convergent and discriminant validities are established. Structural models findings revealed that narcissism antagonism and emotional intelligence were not mediated between narcissism and workplace incivility while emotional intelligence also does not play any mediating role between sadism and workplace incivility. This implies that emotional intelligence has no role in decreasing and reducing workplace uncivil behavior.